1978
DOI: 10.1007/bf00273772
|View full text |Cite
|
Sign up to set email alerts
|

Direct and maternal genetic effects on body weight maturing patterns in mice

Abstract: Direct and maternal genetic effects were evaluated for maturing patterns of body weight in mice using a crossfostering design. Crossfostering was performed in one group using dams from populations selected for rapid growth rate (M16 and H6) and their reciprocal F1. crosses. A second crossfostering group consisted of dams from the respective control populations (ICR and C2) and their reciprocal F1. 's. Population differences were partitioned into direct and maternal effects due to genetic origin, correlated sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A number of researchers have reported significant heterosis for pre-and postweaning body weights and weight gains (Eisen, 1973;Bakker et al, 1976;Nagai et al, 1976). Williams et al (1978) observed significant heterosis for degree of maturity, absolute maturing rate and relative maturing rate at various pre-and postweaning ages.…”
Section: Growth Pattern Of the Mousementioning
confidence: 84%
See 1 more Smart Citation
“…A number of researchers have reported significant heterosis for pre-and postweaning body weights and weight gains (Eisen, 1973;Bakker et al, 1976;Nagai et al, 1976). Williams et al (1978) observed significant heterosis for degree of maturity, absolute maturing rate and relative maturing rate at various pre-and postweaning ages.…”
Section: Growth Pattern Of the Mousementioning
confidence: 84%
“…Some researchers (Nagai et al, 1971;Eisen, 1973;Hayes and Eisen, 1979) have compared the performance of two or three lines of mice for direct and postnatal maternal genetic effects on weights and weight gains at different ages. A few attempts were made to partition the direct or correlated responses into direct and maternal genetic effects (individual and maternal additive) and direct and maternal heterosis (Eisen, 1973;Bakker et al, 1976;Nagai et al, 1976;Williams et al, 1978). In general, the results of these studies indicate that, although maternal genetic effects were significant at preweaning ages, the direct genetic effects were important at all ages.…”
Section: Maternal Effects On Growth and Body Compositionmentioning
confidence: 99%
“…In crossfostering studies, EL OKSH et al (1967) and NAGAI (1971) reported that variation among postnatal dams accounted for 63 to 68 %, of the phenotypic variation in body weight of mice at 12 to 14 d of age. WILLIAMS et al (1978) also reported substantial maternal eftects on maturing patterns among selected mouse lines. These results suggest that the changes in growth patterns between intake lines may be related to changes in maternal ability.…”
Section: Discussionmentioning
confidence: 90%